Francis Muthoni talks to Radio IITA about the value of applying GIS tools in agricultural research - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
Francis Muthoni, IITA GIS Specialist working for the Africa RISING (Research In Sustainable Intensification for the Next Generation) project, talks about the value of geographic information systems (GIS) for Agricultural research in a studio interview with Radio IITA held on 23 August 2021.